The Relationship between the Harmful Algal Blooms (HABs) Phenomenon with Nutrients at Shrimp Farms and Fish Cage Culture Sites in Pesawaran District Lampung Bay - Hasani, Qadar; Adiwilaga, Enan Mulyana; Pratiwi, Niken Tunjung Murti (Makara Journal of Science, 2012)
The phenomenon of harmful algal blooms (HABs) in the Lampung Bay has been reported by many researchers. The occurrence of HABs may be due to the increase of nutrient (N and P) as results of waste water of aquaculture (shrimp farms, hatcheries and fish cage farms). This study aimed to determine the relationship between N and P concentrations in some aquaculture sites with harmful algal blooms. The analysis revealed the differences concentration of N and P at each different shrimp farms and fish cage farms sites (Hurun, Sidodadi, Ringgung, and Cikunyinyi Bay). The result showed that the increase of N and P concentration were followed by the increase of harmful phytoplankton populations. High density HABs were found in this study, such as: Ceratium furca with the highest density at 5.314 x 106 cells/l, Trichodesmium erithraeum 1.05 x 105 cells/l and Noctiluca scintilans 5.99 x 104 cells/l. The Multiple regression and canonical corelation analysis (CCA) also indicated a strong positive relationship between N and P with the HABs at the shrimp farms and fish cage farms sites in the Lampung Bay.